Data Warehouse Design for Educational Data with Data Mining Application - Mukhtar, Nura (2010)
Large data is stored in the data bases in Secondary Schools, which contain student's demographic and Examination Information. There is a need of these data to be integrated in one place. This study analyses the application of Data warehouse and Data mining application on data of student's previous peformance on subject they have took. Where by the data from three Secondary schools were extracted, transformed and loaded into data warehouse. This study also builds student's performance multidimensional cube for each school, a Data mining model was build based on multidimensional cube designed using Microsoft Neural Network as a Data mining tool to predict the Student's performance in their SPM Exam based on their previous subjects performance. The result shows that subject BI from Sama Gagah Secondary School have the highest prediction.